PENGEMBANGAN MEDIA FLASHCARD AKSARA MBOJO UNTUK MENGUATKAN PROFIL PELAJAR PANCASILA SISWA KELAS V SDN 1 TEKE - Nur Fadilah; Khairun Nisa; Ilham Handika; Muhammad Tahir (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to develop media in the form of Mbojo Script flashcards to strengthen the Pancasila Student Profile, especially the global diversity dimension in grade V students of SDN 1 Teke. This research uses the Research and Development (R&D) method with a 4D development model (Define, Design, Develop, Disseminate). This research was carried out at SDN 1 Teke by involving students in class V. Media validation was carried out by media experts and material experts as well as the response of teachers and students as product users. The validation results of media experts obtained a percentage of 98% in the very feasible category and the validation of material experts obtained a percentage of 98% in the very feasible category, while the teacher's response was 86%, while the students' response in the small group trial with a percentage of 91.7% in the very practical category and the student response in the large group trial with a percentage of 96.3% in the very practical category. Therefore, it can be concluded based on the results of the research that the Mbojo script flashcard media to strengthen the Pancasila student profile of Class V students of SDN 1 Teke is very feasible and practical to be used in the learning process and to strengthen the profile of Pancasila students